The effect of temperature on cadmium oxide (CdO) nanoparticles produced by synchrotron radiation in the human cancer cells, tissues and tumors - Heidari, Alireza (International Journal of Advanced Chemistry, 2018)
In this work, the effect of temperature of the ablation environment on the properties of Cadmium Oxide (CdO) nanoparticles produced by synchrotron radiation is investigated. To produce nanoparticles, synchrotron radiation pulse with 1064 (nm) wavelength is used to emit Cadmium in the human cancer cells, tissues and tumors. All test parameters were kept constant and human cancer cells, tissues and tumors temperature was changed to produce samples at 20°C and 65°C. Then, ATR–FTIR, XRD, TEM and UV–Visible spectroscopy analyses were performed to investigate their properties. The results show that the size of nanoparticles is increased by increase in temperature of ablation environment. In addition, in the current experimental research, Gold (Au)–Cadmium Oxide (CdO) alloy is created at the size of nano. In this regard, same volume of Gold and Cadmium Oxide (CdO) solutions were mixed together and emitted by the synchrotron radiation pulse with wavelength of 532 (nm). The Gold and Cadmium Oxide (CdO) solutions have been produced, separately, using synchrotron radiation ablation process. To produce them, synchrotron radiation pulse with wavelength of 1064 (nm) and pulse width of 7 (ns) and repeating frequency of 5 (Hz) was used. The results show that synchrotron radiation emission with wavelength of 532 (nm) is an appropriate method for producing Gold compounds in the size of nano.